The antimicrobial properties of the glycolic extract of Casearia sylvestris Sw. in monotypic biofilm of Candida albicans and Candida glabrata (Research, Society and Development, 2022)
Objectives: The resistance of microorganisms to the misuse of drugs is currently one of the public health problems, making research on natural compounds with antimicrobial activity, such as Casearia sylvestris, necessary. This study aimed to evaluate the antimicrobial activity of the glycolic extract of Casearia sylvestris on standard strains of Candida albicans (ATCC 18804) and Candida glabrata (ATCC 9030) in planktonic cultures, verifying the minimum inhibitory concentration and minimum microbicide concentration (MIC and CMM) and also its action on biofilms. Methodology: The glycolic extract of C. sylvestris, of commercial origin, was obtained at a concentration of 200 mg/ml (20%) eluted in 80% of propylene glycol. The MIC and CMM values were determined by the broth microdilution method, according to the Clinical and Laboratory Standards Institute (CLSI), standards M27-A2, with modifications. Then, tests were started on 48h monotypic biofilms, with broth change every 24h, of these microorganisms. After undergoing treatments, the biofilm was prepared for the MTT metabolic test. Results: Candida albicans presented MMC at 50 mg/mL, in Candida glabrata there was no MIC and MMC. In the MTT test the results showed effectiveness of the concentration of 25 mg/mL on Candida glabrata, with a reduction of ≥ 29%, in Candida albicans there were no significant results in the analyzed concentrations. Conclusion: The extract hawed an antimicrobial effect against the tested genre. We also emphasize the importance of in vitro and in vivo tests that corroborate the results presented, in order to increase the basis for the application of the extract.